Chlorophyll a Concentration of Phytoplankton during the Cruise of the 48th Japanese Antarctic Research Expedition in 2006-2007 - Kasamatsu, Nobue; Han, Dong-Hoon; Kudoh, Sakae; Fukuchi, Mitsuo (National Institute of Polar Research, 2007)
P(論文) departmental bulletin paper